Influencing Factors of Internet Usage among Women Entrepreneurs - Ahmad, Azhar (Archives of Business Research, 2018)
Malaysian women are recognised to play a major role in the growth of local Small and Medium Enterprises (SMEs). Previous studies show that ICT is an important factor influencing the growth of women entrepreneurs in Malaysia. This study aims to analyse the Internet skills among women entrepreneurs and the influencing factors encouraging them to use Internet in their business activities. A survey was conducted on 51 women entrepreneurs in Putrajaya, Malaysia. The study showed positive relationship between Internet skills and influencing factors on Internet usage in business. However, only factors “ease of use” and “social influence” have significant relationships toward the intention of Internet usage among the entrepreneurs. Thus, Internet usage among the entrepreneurs are inflluenced by the ease of use of technology and social factors. Social influence from media, family members and fellow entrepreneurs have pushed these business women to use Internet as a new medium to improve their business activities.